2018
DOI: 10.1177/1533033818806318
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Hypofractionated Radiotherapy Versus Stereotactic Body Radiotherapy for the Treatment of Stage I Nonsmall Cell Lung Cancer—A Single Institution Experience With Long-Term Follow-Up

Abstract: Purpose:Although stereotactic body radiation therapy is one of the standard treatments for stage I nonsmall cell lung cancer, in the case of central tumors it carries the risk of severe adverse events for serial organs. Accelerated hypofractionated radiotherapy is considered a reasonable alternative to treat central tumors. We have been treating central tumors with accelerated hypofractionated radiotherapy using a 75 Gy/25 fr/5 weeks regimen, and we compared the results with those of stereotactic body radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Hypofractionated schedules may be considered in these cases. Karasawa et al reported that accelerated hypofractionated radiotherapy with 75 Gy in 25 fractions at the isocenter, which is considered equivalent to 62.5 Gy in 25 fractions prescribed at PTV D95%, is promising in that it can achieve LC and survival results similar to SBRT, and it can control both central and peripheral stage I NSCLC without any serious organ toxicities [ 44 ].…”
Section: Differences According To the Primary Tumor: Non-lung Primary...mentioning
confidence: 99%
“…Hypofractionated schedules may be considered in these cases. Karasawa et al reported that accelerated hypofractionated radiotherapy with 75 Gy in 25 fractions at the isocenter, which is considered equivalent to 62.5 Gy in 25 fractions prescribed at PTV D95%, is promising in that it can achieve LC and survival results similar to SBRT, and it can control both central and peripheral stage I NSCLC without any serious organ toxicities [ 44 ].…”
Section: Differences According To the Primary Tumor: Non-lung Primary...mentioning
confidence: 99%
“…S PS 2005–2013 65 32/33 Both 71.8 Deep inspiration breath hold 4D-CT, MIP NR 50/–/50 4 NR LA, 6–12 CB or NCB NR 112.5/–/112.5/– 86 95.4 Cummings (2018) [ 23 ] U. S PS 2007–2015 65 98 30/35 44/54 NR 76 77 ITV > 0.5 cm: respiratory gating CTV = GTV, 4D-CT 5 30/–/30 50/50/40 1 5 1 fraction per day LA, 11 NCB No 120/120/–/– 100/100/72/86 24 40 84.0 82.8 karasawa (2018) [ 24 ] Japan RS 2003–2010 56 39/17 No 79 SBF Long-scan-time CT, margin 5 mm 5 48/48/42 4 Total 1 week LA, 6MV Yes 105.6/105.6/86.1/95.9 127 78.2 Ma (2018) [ 25 ] U. S RS 2007–2015 ...…”
Section: Resultsmentioning
confidence: 99%
“…At present, there is no uniform standard for the prescription dose method of SBRT. Some prescription doses are defined as isocenter dose [ 23 , 24 , 34 ], and some are defined as isodose lines surrounding 95% PTV volume [ 32 , 35 , 36 ]. At the same time, the degrees of heterogeneity of dose in PTV for different centers may be diverse.…”
Section: Discussionmentioning
confidence: 99%
“…The normal tissues evaluated in this study are esophagus, aorta, heart, pulmonary artery, and trachea, and the D 1cc , D 5cc , D 10cc , and D 15cc of these organs were examined on the basis of previous clinical trials. 2 , 3 A total of 300 plans (20 cases × 3 MLC speed constraints × 5 error plans) were investigated.…”
Section: Methodsmentioning
confidence: 99%
“… 1 In general, SBRT is often performed on peripheral tumors, although some reports have described its use for central tumors. 2 , 3 In cases involving central lung tumors, the tumor is located in close proximity to the bronchi, heart, and great vessels, increasing the likelihood of toxicity. Thus, treatment planning with careful attention to these doses is essential in such cases.…”
Section: Introductionmentioning
confidence: 99%